Rasio legis eksistensi pengadilan tindak pidana korupsi dalam sistem peradilan pidana Indonesia - Ahmad Fauzi; Abdul Madjid; Nurini Aprilianda; Prija Djatmika (University of Merdeka Malang, 2021)
Corruption if allowed to have a real economic impact, namely unequal income and increasing poverty Corruption is a common problem that occurs in almost every country, the modus operandi of corruption is to use the authority and power to take advantage for personal gain or third parties, therefore to overcome corruption crimes need a way to tackle corruption crimes. This research is a legal research using the socio-normative approach. The data used are primary data and secondary data which were analyzed using quantitative analysis. The main aspect in tackling corruption crimes is to use a law enforcement approach, one of the approaches to law enforcement is to create a Corruption Crime Court as regulated in Law No. 46 of 2009 concerning the Corruption Crime Court as an institution in charge of examining and deciding cases of criminal acts of corruption. The position of the court for criminal acts of corruption actually has a strong legal standing in the Indonesian criminal justice system, and its existence is very important and urgent in tackling corruption crimes in Indonesia.How to cite item: Fauzi, A., Madjid, A., Aprilianda, N., Djatmika, P. (2021). Rasiolegis eksistensi pengadilan tindak pidana korupsi dalam sistem peradilan pidana Indonesia. Jurnal Cakrawala Hukum, 12(1), 11-20. doi:10.26905/idjch.v12i1.5779.